Effect of Labeling with Iron Oxide Particles or Nanodiamonds on the Functionality of Adipose-Derived Mesenchymal Stem Cells - Blaber, Sinead P. (Public Library of Science, 2013)
Stem cells are increasingly the focus of translational research as well as having emerging roles in human cellular therapy. To support these uses there is a need for improved methods for in vivo cell localization and tracking. In this study, we examined the effects of cell labeling on the in vitro functionality of human adipose-derived mesenchymal stem cells. Our results provide a basis for future in vivo studies investigating implanted cell fate and longevity. In particular, we investigated the effects of two different particles: micron-sized (∼0.9 µm) fluorescently labeled (Dragon Green) superparamagnetic iron oxide particles (M-SPIO particles); and, carboxylated nanodiamonds of ∼0.25 µm in size. The effects of labeling on the functionality of adipose-derived MSCs were assessed by in vitro morphology, osteogenic and adipogenic differentiation potential, CD marker expression, cytokine secretion profiling and quantitative proteomics of the intra-cellular proteome. The differentiation and CD marker assays for stem-like functionality were not altered upon label incorporation and no secreted or intra-cellular protein changes indicative of stress or toxicity were detected. These in vitro results indicate that the M-SPIO particles and nanodiamonds investigated in this study are biocompatible with MSCs and therefore would be suitable labels for cell localization and tracking in vivo.